Temperature-responsive chromatographic separation of amino acid phenylthiohydantions using aqueous media as the mobile phase - Kanazawa, H; Sunamoto, T; Matsushima, Y; Kikuchi, A; Okano, T (Analytical chemistry (Washington), 2000)
Recently, green chemistry has become one of the most important subjects of science for environmental pollution prevention. Here, we report development of a novel chromatographic technology for phenylthiohydantoin (PTH)-amino acid analyses in which only aqueous solution is used as the mobile phase. We have devised HPLC adsorbents (stationary phase) by modifying the surfaces of microparticulate silica gel using functional polymers. The thermoresponsive copolymer, poly(N-isopropylacrylamide-co-n-butyl methacrylate) (IBc) was used to modify the silica stationary phase surfaces. This polymer-grafted surface exhibits temperature-regulated hydrophilic/hydrophobic property changes in water. PTH-amino acid interactions with this surface are readily modulated by changing the column temperature using an isocratic aqueous mobile phase. Increasing hydrophobic interactions between more hydrophobic PTH-amino acids with hydrophobized polymer-grafted surfaces at elevated mobile phase temperatures is used for the effective separation of PTH-amino acids in aqueous solution. This study is aimed at the development of novel separation processes, which are also environmentally benign, for use with biochemical substances in order to meet the growing needs of the life sciences and biotechnology. The method is useful for various separations in life science so that proteins can maintain their biological activity and enzymes, their enzymatic activity.